The importance of paraoxonase 1 activity in chronic kidney disease - Elisabeth C. Samouilidou; Augustina Liaouri; Vassilis Kostopoulos; Dimitris Nikas; Eirini Grapsa (Renal Failure)
Paraoxonase 1 (PON1) is one of the most significant antioxidative enzymes associated with high-density lipoprotein (HDL). It has been proved that is involved in the pathogenesis of many diseases including chronic kidney disease (CKD). The association between PON1 and CKD seems to be mutual, such that the disease produces a significant decrease in PON1 activity levels, while the genetics of PON1 may affect the risk of susceptibility to CKD. Recent studies reveal that the decrease in serum PON1 activity observed in non-dialyzed and dialyzed CKD patients as well as in renal transplant (RT) patients is linked to an increased vulnerability to atherosclerosis. We intend to summarize current literature concerning PON1 activity in CKD, highlighting on the main determinants of PON1 activity, its association with oxidative stress, the impact of its genetic polymorphism on the disease development, the effect of drugs and nutritional state. Furthermore, evidence supporting the implication of reduced PON1 activity in the incident of cardiovascular disease in CKD patients, is also examined. It appears that despite the lack of standardization of PON1 activity measurement, PON1 remains a valuable biomarker for the researchers through the last decades, which contributes to the assessment of the antioxidant status having prognostic benefit on adverse clinical outcomes at various stages and etiologies of kidney disease.